Grundtvig og folkehøjskolen i dag: Fløjkrig og vekselvirkning - Wigh-Poulsen, Henrik (Grundtvig-Studier, 2004)
Grundtvig og folkehøjskolen i dag: Debatindlæg fra tre yngre Grundtvig-forskere om den grundtvigske arv i højskoledebatten i begyndelsen af 2004. Bidragene stammer fra et fyraftensmøde i Højskolernes Hus, Nytorv, København [Grundtvig and the Folk-Highschool today: Contributions to a Debate from three younger Grundtvig- Scholars, in Connection with the national Debate upon the Grundtvig-Legacy in the Folk-Highschool early in 2004. The Contributions stem from an Evening Meeting in Højskolernes Hus, Nytorv, Copenhagen] By Henrik Wigh-Poulsen, Jes Fabricius Møller and Kim Arne Pedersen Henrik Wigh-Poulsen (Grundtvig Academy) sketches out the way in which the Grundtvig legacy, having at first been a force for religious and political transformation, has become a national gene-code by becoming identified with Danishness. However, this is not felt to be a victory within the Grundtvigian movement where almost from the start a worry about watering-down and a desire to get back to the wellsprings can be traced. Instead of worrying, a job of reconstruing ought to be addressed. In our post-postmodem age, the inherited legacy is no longer taken as given but has to be reformulated without use of the received terminology. The annexation of Grundtvig by Danish newnationalism and the modem folk-highschoofs critical relationship to the inheritance from him make this problematic, but with a startingpoint in Grundtvig’s conception of Christianity one may point to Grundtvig’s openness, founded upon his creation-theology, towards the present and the future and that interaction between Christianity and culture, tradition and renewal, which ensue from it. Jes Fabricius Møller, taking as his starting-point the enthusiasm of certain folk-highschool people for qualification-orientated education, combined with criticism of Grundtvig, suggests that this group of people’s current break with Grundtvig is not inconsistent with the history of the folk-highschools following the Second World War, when interest gravitated towards life-philosophy, theology and literature. Furthermore, Grundtvig has suffered the fate of been overshadowed by the Grundtvig-myth, a relationship which has partly to do with the compartmentalised nature of Grundtvig’s writings, and partly with the compartmentalisation of the Grundtvigian movement. Here, Grundtvig functions as a mythic gathering-point which English Summaries / danske resuméer overshadows the real Grundtvig. Grundtvig is of significance not because of the effectiveness of his specific message, but because he made himself effective and thereby became an historical premise for the present. Kim Arne Pedersen, in an extension of the study-group “A new view upon Grundtvig” within the Danish folk-highschools, sketches an outline for a new interpretation of the Grundtvigian vision of the highschool. The objective is that the highschools should keep up with the circumstances of the times without capitulating to their conditions, but concretely to formulate a third way between new nationalism’s exploitation of Grundtvig and his repudiation by Danish intellectuals and highschool people: that is, on the one hand a nationalistic Grundtvig, and on the other hand the Danish education system’s focus upon the concept of qualification-attainment [>kompetence-begrebet], which is here to be understood as being in harmony with the present time’s focus upon power relationships as the determinant within human relationships. The history of Grundtvig’s influence and the debate among Grundtvig scholars form a background for the third way. In opposition to acceptance of power relationships as foundational, an extension of Martin Buber is brought to bear upon the dialogue. Grundtvig is seen as a part of modernity, and against the background of the Grundtvigian concepts of converse [samtale] and interaction [vekselvirkning] the Grundtvigian concept of life-enlightenment [livsoplysningsbegreb] is construed out of the human relationship to God within a radical freedom and with space for the miracle and the unexpected which breaks through into human life through this dialogue. The Grundtvigian concept of national communality [folkelighed] is construed, in opposition to theories of social-constructivist nationalism, along the lines of Adrian Hastings’ understanding of “nation” as a concept coming into existence via Christianity in the medieval and early modem periods. Global changes mean that today national communality [folkelighed] is indeed to be understood against the background of the national culture, but also, simultaneously, as an imperative, a project, rather than as a description of a pre-established reality.